Crystal structure of (E)-7-methoxy-2-((6-methoxypyridin-2-yl)methylene)-tetralone, C18H17NO3 - Wang Lei; Meng Qing-Guo; Hou Gui-Ge (Zeitschrift für Kristallographie - New Crystal Structures)
C18H17NO3, triclinic, P1‾$P‾{1}$ (no. 2), a = 4.0929(4) Å, b = 12.9527(11) Å, c = 14.4228(12) Å, α = 70.171(8)°, β = 87.229(8)°, γ = 87.567(8)°, V = 718.16(12) Å3, Z = 2, Rgt(F) = 0.0549, wRref(F2) = 0.1526, T = 99.9(3) K.